Orthorexia Nervosa - unhealthy obsession on healthy lifestyle - Jędrasek, Aleksandra; Wojtyła, Klaudia; Barg, Marta; Łęska, Aleksandra (Quality in Sport, 2024)
Introduction: Eating disorders have expanded rapidly in recent years, with social media platforms like Instagram and TikTok playing a significant role. These platforms often showcase idealized images of healthy eating and body image, exposing young people to an overwhelming amount of information. This overstimulation can contribute to the development of various eating disorders. In our study, we focus particularly on orthorexia nervosa. Review methods: Our study was conducted as a literature review, with data gathered from PubMed and Embase. The state of knowledge: Orthorexia Nervosa (ON), introduced by Steven Bratman in 1997, could be defined as an unhealthy obsession with healthy eating. This obsession leads to strict dietary restrictions, where individuals often exclude certain food types, such as preservatives and GMOs, and experience significant stress and anxiety over food choices, planning, and preparation methods. The fixation on food purity can result in social isolation, anxiety, and major disruptions to daily life. In comparison to other eating disorders like anorexia nervosa and obsessive-compulsive disorder (OCD), ON is characterized by its focus on food quality rather than body image or weight. Conclusions: The classification of orthorexia as a mental disorder and the need for its recognition in DSM-5 are still debated. However, growing concern about its impact on mental and physical health has led to increased research and awareness.